Prasugrel inhibits platelet-leukocyte interaction and reduces inflammatory markers in a model of endotoxic shock in the mouse - Totani, Licia; Dell’Elba, Giuseppe; Martelli, Nicola; Di Santo, Angelomaria; Piccoli, Antonio; Amore, Concetta; Evangelista, Virgilio (Thrombosis and Haemostasis, 2012)
Prasugrel, through its active metabolite, reduces atherothrombosis and its clinical manifestations by inhibiting platelet activation and aggregation. Platelets also contribute to inflammation through interaction with different classes of leukocytes. We investigated whether the inhibitory effect of prasugrel on platelets also counteract inflammatory responses. The effect of prasugrel active metabolite, R-138727, was investigated on platelet P-selectin expression, platelet adhesion to polymorphonuclear leukocytes (PMN) and monocytes (MN) and Mac-1 expression in PMN and MN, in vitro, in human cells. The ex vivo effect of prasugrel administration on P-selectin, thromboxane (TXB)2 formation, platelet-PMN conjugates and Mac-1 expression in PMN triggered by PAR-4 agonist peptide was examined in whole blood from healthy mice as well as from mice in which an acute inflammatory reaction was induced by treatment with endotoxin. The effect of prasugrel on inflammatory markers in endotoxin-treated animals was also tested in vivo. R-138727 inhibited agonist-stimulated expression of platelet P-selectin, platelet-PMN and platelet-MN adhesion and platelet-dependent Mac-1 expression in leukocytes. Addition of aspirin did not modify the inhibitory effect elicited by R-138727. Treatment of mice with prasugrel resulted in a profound inhibition of platelet P-selectin expression, TXB2 production, platelet-PMN adhesion and Mac-1 expression in PMN induced by ex vivo stimulation with PAR-4 agonist peptide of whole blood from healthy or endotoxin-treated mice. Measurement of markers revealed that prasugrel reduced TXB2 and tumour necrosis factor-α synthesis and increased nitric oxide metabolites in endotoxin-treated mice in vivo. In conclusion, prasugrel reduces platelet interactions with PMN and MN. Through these effects prasugrel may curb platelet-mediated inflammatory responses.
Keywords: Inflammation; monocytes; neutrophils; platelets; prasugrel; P-selectin